Tanggung Jawab Pidana dan Uang Pengganti dalam Kasus Pencucian Uang Korupsi di Indonesia - Januar Rasito; Kristiawanto Kristiawanto; Mohamad Ismed (Jurnal Penelitian Hukum Legalitas, 2023)
This research discusses evidence in corruption money laundering cases in Indonesia, focusing on the use of reverse burden of proof. This burden of proof is applied primarily to the assets of the defendant in corruption cases. However, the use of this reverse burden of proof still raises uncertainties in its implementation, especially in identifying assets that are not defendants, and can have an impact on the ownership rights of the defendant's assets. This research uses a normative juridical method with interpretative analysis to investigate the complexity of the evidentiary mechanism. The results show that the defendant must prove that his/her assets are not the proceeds of a criminal offense to retain the right to the assets, otherwise, the assets will be confiscated by the state. Therefore, further clarification is needed in the relevant laws to improve clarity and fairness in the application of the reverse burden of proof in corruption and money laundering cases.